ℋ∞ optimization of an integral force feedback controller. (September 2019) - Zhao, G.; Paknejad, A.; Deraemaeker, A.; Collette, C.
This paper studies the performance of the classical integral force feedback (IFF) controller for suppressing the forced response of a single degree of freedom (SDOF) system. An ℋ∞ optimization criterion is used to derive the optimal feedback gain of the IFF controller contributed as a complement for the state of the art. This optimal gain is calculated in the closed-form based on a SDOF system which is then applied to a two degrees of freedom system to study its adaptability. It is found that the ℋ∞ optimal gain can be easily transposed into multi-degrees of freedom applications without introducing too many errors. An equivalent mechanical model is also developed to enable a straightforward interpretation of the physics behind the IFF controller.